Studies on Germination and Seed-borne Fungi of Some Forest Tree Species and their Control - Purohit, Mamta; , Jamaluddin; Mishra, G. P. (Indian Forester, 1998)
The germination tests were performed with 4 different tree species in laboratory. The purity percentage and number of pure seeds per kg were also calculated. Lagerstroemia parviflora showed poor germination even from the fresh lots while other species showed high germination percentage. Over all 12 fungi were recorded in blotter as well as potato-dextrose-agar test which varies from species to species. Out of 4 fungicides used for seed treatment Bavistin, Dithane M-45 and Thyride @ 3 gm/kg seed weight were highly effective in controlling the seed myeoflora. It is recommended that the seeds of B. monosperma, D. strictus, L. parviflora and P. pinnata may be treated with the above light dose of fungicides for controlling fungal infestation.